(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the theoretical and methodological foundations of the study of the process of implementation of the norms of international law governing objects of intellectual property in national legislation and implementation mechanisms. It is analyzed the norms of international law in the field of intellectual property from the point of view of further implementation in national legislation